Pseudotumor Tuberculosis Of Liver: A Rare Entity - Soufi, Mehdi; Kharrasse, Ghizlane; wafae, Khanoussi; Ismaili, Zahi; El haroudi, Tijani; Bouziane, Mohammed (Journal of Spleen And Liver Research, 2015)
We present a rare case of a 46-year-old man who presented with recurrent fever and abdominal pain without other symptoms. Laboratory data were no specific for diagnosis. Abdominal imaging revealed a pseudotumor liver. A diagnosis of isolated liver tuberculosis with abscess component was confirmed with US-guided liver biopsy and histopathological examination. The patient received antibacillous drugs with success.
Keywords: tuberculosis; Liver; pseudotumor; antibacillous drugs.